-9(-6s-9+5c)=

Simple and best practice solution for -9(-6s-9+5c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(-6s-9+5c)= equation:


Simplifying
-9(-6s + -9 + 5c) = 0

Reorder the terms:
-9(-9 + 5c + -6s) = 0
(-9 * -9 + 5c * -9 + -6s * -9) = 0
(81 + -45c + 54s) = 0

Solving
81 + -45c + 54s = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-81' to each side of the equation.
81 + -45c + -81 + 54s = 0 + -81

Reorder the terms:
81 + -81 + -45c + 54s = 0 + -81

Combine like terms: 81 + -81 = 0
0 + -45c + 54s = 0 + -81
-45c + 54s = 0 + -81

Combine like terms: 0 + -81 = -81
-45c + 54s = -81

Add '-54s' to each side of the equation.
-45c + 54s + -54s = -81 + -54s

Combine like terms: 54s + -54s = 0
-45c + 0 = -81 + -54s
-45c = -81 + -54s

Divide each side by '-45'.
c = 1.8 + 1.2s

Simplifying
c = 1.8 + 1.2s

See similar equations:

| (4p^4/8q^5)^4 | | H=a+7b+3c | | 4x+12x-5=25+2 | | 2x-(x+4)=4-(x+2) | | 3(ln)(4x)=12 | | 2x-(c+4)=4-(x+2) | | 3x-9=84/14 | | 45.183+k-20=-15 | | 3(y-2)=(4+y) | | 2-1/2*4/5= | | r(r+5)=104 | | (x^2-16)(x^2-49)=0 | | 93x-22=71 | | 128(3)= | | 3x=384 | | 906x-42=604 | | (x-3)(2x-5)=0 | | -4-2x+2-x= | | 2n^2-20n+50= | | 2p+3-5p=-4p+7 | | 300x-0.44=500x+0.64 | | (x-1)(x^2+8x+15)=0 | | 2x+5-4x-12-6x-17=180 | | -2x+10=2x+2 | | -9.85+1.98y-1.19-3.68y= | | 6/9 | | 10(8a+3)= | | 3/2=12/3y-12/1 | | 3x-14.2=x | | 9-2+3*5= | | 19(8c-1)-4=150c+19 | | -20(5m-9n+3p)= |

Equations solver categories